Exploring extracellular vesicles metrics in diabetic retinopathy vitreous, aqueous, and plasma - Kleber S. Ribeiro; Carmen Luz Pessuti; Heloisa Nascimento; Rubens Jr Belfort; Alessandra G. Commodaro; Ana Claudia T. Torrecilhas (The Pan-American Journal of Ophthalmology)
Purpose: Extracellular vesicles (EVs) were obtained from ocular samples and plasma of diabetic retinopathy (DR) patients who were having cataract and/or vitrectomy surgeries. Methods: Aqueous, vitreous, and plasma were collected from six patients with proliferative DR (PDR), also aqueous and plasma were collected from seven patients with non-PDR (NPDR), and seven patients with cataract (control group). EVs were isolated using the membrane affinity column method. Nanoparticle tracking analysis technique was used to measure the size and concentration of particles. Results: The mean size of EVs in aqueous was smaller in the PDR group comparing with the other two groups (P < 0.05). Besides, EVs concentration in plasma was higher in the PDR group than in the NPDR group (P < 0.05). Conclusion: We successfully isolated and measured EVs in ocular samples and plasma from DR patients. Further studies must be conducted to identify protein and molecular contents to better understand the role of particles in the pathophysiology of DR and their potential as a biomarker or medicinal target.